Strategies for Effective Resolution of Disputes in International Commercial Contracts - Chikaome Chimara Imediegwu; Okeoghene Elebe; Andikan Udofot Umana; Opeyemi Morenike Filani; Muritala Omeiza Umar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This review paper explores the strategies for effectively resolving disputes in international commercial contracts. It highlights the importance of clear and precise contract drafting as a preventive measure, emphasizing how well-defined terms and conditions can minimize the risk of conflicts. The paper also examines the role of negotiation and pre-arbitration steps, such as mediation, in resolving disputes amicably and preserving business relationships. The selection of the appropriate forum and qualified arbitrators is discussed as a critical factor in influencing the fairness and efficiency of dispute resolution. Furthermore, the paper analyzes the emerging role of technology, particularly online dispute resolution (ODR), in facilitating faster and more cost-effective processes. The review concludes with practical recommendations for legal practitioners and businesses, and it anticipates future trends that may further impact international dispute resolution, including technological advancements and the potential harmonization of international legal frameworks.